2022
DOI: 10.1210/jendso/bvac132
|View full text |Cite
|
Sign up to set email alerts
|

Castration of Male Mice Induces Metabolic Remodeling of the Heart

Abstract: Androgen deprivation therapy of prostate cancer, which suppresses serum testosterone to castrate levels, is associated with increased risk of heart failure. Here we tested the hypothesis that castration alters cardiac energy substrate uptake, which is tightly coupled to the regulation of cardiac structure and function. Short-term (3-4 weeks) surgical castration of male mice reduced the relative heart weight. While castration did not affect cardiac function in unstressed conditions, we observed reductions in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A cross-sectional study assessing hs-cTn in trans people on GAHT for >12 months found that median concentrations of hs-cTn in trans men were similar to cisgender men, and trans women were similar to cisgender women ( 120 ). These findings are concordant with animal models demonstrating androgen deprivation in male mice induces metabolic remodeling of the heart with reduced cardiac mass and impaired cardiac output during stress ( 121 ).…”
Section: Cardiorespiratory Function In Trans Womensupporting
confidence: 86%
“…A cross-sectional study assessing hs-cTn in trans people on GAHT for >12 months found that median concentrations of hs-cTn in trans men were similar to cisgender men, and trans women were similar to cisgender women ( 120 ). These findings are concordant with animal models demonstrating androgen deprivation in male mice induces metabolic remodeling of the heart with reduced cardiac mass and impaired cardiac output during stress ( 121 ).…”
Section: Cardiorespiratory Function In Trans Womensupporting
confidence: 86%
“…While the practice of castration, known to prolong the lifespan in domesticated dogs and cats in veterinary medicine 69 , offers intriguing possibilities for aging research, its potential has only recently begun to be explored. However, existing studies on this subject are isolated and primarily focus on the decelerated methylation clock and lifespan extension following castration, offering scant insights into the underlying molecular regulations 11, 12, 70, 71 . Consequently, the utilities of castration as a model to dissect sex differences in healthy aging and to elucidate the underlying molecular mechanisms remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, survival assays in genetically diverse mice reveal that castration extends longevity, implicating post- pubertal testicular actions as key determinants of sex differences in lifespan and growth trajectories [10]. Moreover, castration has been shown to induce metabolic remodeling in male hearts [67] and mitigate the formation of aging-induced abdominal aortic aneurysms [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation